2014
DOI: 10.1021/es500319q
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry of Enols: A Theoretical Study of the Vinyl Alcohol + OH + O2 Reaction Mechanism

Abstract: Enols are emerging as trace atmospheric components that may play a significant role in the formation of organic acids in the atmosphere. We have investigated the hydroxyl radical ((•)OH) initiated oxidation chemistry of the simplest enol, vinyl alcohol (ethenol, CH2═CHOH), using quantum chemical calculations and energy-grained master equation simulations. A lifetime of around 4 h was determined for vinyl alcohol in the presence of tropospheric levels of (•)OH. The reaction proceeds by (•)OH addition at both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
102
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(114 citation statements)
references
References 42 publications
7
102
3
2
Order By: Relevance
“…Biomass burning emissions are derived from the GFEDv3 (Global Fire Emissions Database) database (van der Werf et al, 2010). The GEOS-Chem chemical mechanism has been updated here to include explicit treatment of Criegee intermediates as well as the recently proposed production of vinyl alcohol (and subsequently HCOOH; Archibald et al, 2007;So et al, 2014) from the keto-enol tautomerization of acetaldehyde (Andrews et al, 2012;Clubb et al, 2012). The latter accounts for some 20 % of the global HCOOH burden in the model, which likely represents an upper limit as our implementation here does not account for losses of vinyl alcohol other than oxidation by OH (So et al, 2014;Karten, 2014;da Silva, 2010).…”
Section: Results From Tes Global Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomass burning emissions are derived from the GFEDv3 (Global Fire Emissions Database) database (van der Werf et al, 2010). The GEOS-Chem chemical mechanism has been updated here to include explicit treatment of Criegee intermediates as well as the recently proposed production of vinyl alcohol (and subsequently HCOOH; Archibald et al, 2007;So et al, 2014) from the keto-enol tautomerization of acetaldehyde (Andrews et al, 2012;Clubb et al, 2012). The latter accounts for some 20 % of the global HCOOH burden in the model, which likely represents an upper limit as our implementation here does not account for losses of vinyl alcohol other than oxidation by OH (So et al, 2014;Karten, 2014;da Silva, 2010).…”
Section: Results From Tes Global Surveysmentioning
confidence: 99%
“…The GEOS-Chem chemical mechanism has been updated here to include explicit treatment of Criegee intermediates as well as the recently proposed production of vinyl alcohol (and subsequently HCOOH; Archibald et al, 2007;So et al, 2014) from the keto-enol tautomerization of acetaldehyde (Andrews et al, 2012;Clubb et al, 2012). The latter accounts for some 20 % of the global HCOOH burden in the model, which likely represents an upper limit as our implementation here does not account for losses of vinyl alcohol other than oxidation by OH (So et al, 2014;Karten, 2014;da Silva, 2010). The resulting HCOOH source totals 55 Tg globally in 2009, including 47 Tg from photochemical production, 4.2 Tg from direct biogenic emissions (including soils), 1.5 Tg from direct fire emissions, and 2.6 Tg from anthropogenic and agricultural sources.…”
Section: Results From Tes Global Surveysmentioning
confidence: 99%
“…[37] Recently, Coggins and Powner [38] demonstrated the synthesis of phosphoenol pyruvate (7), a high energy phosphate found in living organisms, from prebiotic precursors such as glycolaldehyde and glyceraldehyde. Enols have been suggested as important reactive intermediates for the formation of secondary organic aerosols in the atmosphere, [39][40][41][42][43] as enols can readily be oxidized to carboxylic acids in the gas phase. [41,43,44] The fragmentation of molecular precursors presents a suitable entry point to explore the synthesis of enols in the gas phase.…”
mentioning
confidence: 99%
“…Enols have been suggested as important reactive intermediates for the formation of secondary organic aerosols in the atmosphere, [39][40][41][42][43] as enols can readily be oxidized to carboxylic acids in the gas phase. [41,43,44] The fragmentation of molecular precursors presents a suitable entry point to explore the synthesis of enols in the gas phase. As established historically, dicarboxylic acids are attractive enol precursors due to their facile preparation, their tendency to undergo thermal decarboxylation under mild conditions, and their release of an inert and neutral byproduct (Scheme 1).…”
mentioning
confidence: 99%
“…It has been shown that M06-2X can give the best performance without increasing the computational time for the thermochemistry and kinetics calculations Zhao and Truhlar, 2008b). Therefore, it has successfully been applied to simulate the radicalinitiated oxidation of organics in environmental studies (So et al, 2014). The solvent effect of water was considered by continuum solvation model 'SMD' (Marenich et al, 2009).…”
Section: Mechanism Computationmentioning
confidence: 99%